2007
DOI: 10.4049/jimmunol.179.7.4480
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant Protein A Activation of Atypical Protein Kinase C ζ in IκB-α-Dependent Anti-Inflammatory Immune Regulation

Abstract: The pulmonary collectin surfactant protein (SP)-A has a pivotal role in anti-inflammatory modulation of lung immunity. The mechanisms underlying SP-A-mediated inhibition of LPS-induced NF-κB activation in vivo and in vitro are only partially understood. We previously demonstrated that SP-A stabilizes IκB-α, the primary regulator of NF-κB, in alveolar macrophages (AM) both constitutively and in the presence of LPS. In this study, we show that in AM and PBMC from IκB-α knockout/IκB-β knockin mice, SP-A fails to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
24
1

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 66 publications
4
24
1
Order By: Relevance
“…Pharmacological inhibition and transient silencing of PKCz in RAW264.7 cells abolished the effects of SP-A on Rab7 stabilization. In line with this finding, it has been shown previously that PKCz inhibition/knockout had a significant negative effect on SP-A-mediated signaling events (38), pointing to an essential role for PKCz in SP-A-specific modulation of AM function. In contrast, SP-A-enhanced Rab7b stabilization was wortmannin insensitive, and coimmunoprecipitation experiments failed to show an SP-Aenhanced interaction of Rab7b with PKCz, suggesting a signaling pathway distinct from PI3K/PKCz for SP-A-enhanced Rab7b availability.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Pharmacological inhibition and transient silencing of PKCz in RAW264.7 cells abolished the effects of SP-A on Rab7 stabilization. In line with this finding, it has been shown previously that PKCz inhibition/knockout had a significant negative effect on SP-A-mediated signaling events (38), pointing to an essential role for PKCz in SP-A-specific modulation of AM function. In contrast, SP-A-enhanced Rab7b stabilization was wortmannin insensitive, and coimmunoprecipitation experiments failed to show an SP-Aenhanced interaction of Rab7b with PKCz, suggesting a signaling pathway distinct from PI3K/PKCz for SP-A-enhanced Rab7b availability.…”
Section: Discussionsupporting
confidence: 71%
“…This is in contrast with a previous study (77) Several in vitro and in vivo studies have demonstrated that phosphatidylinositol-3,4,5-triphosphate directly activates the atypical PKCs (z, l/i) in a PI3K-dependent manner (78)(79)(80). It was shown that SP-A induces a rapid activation of PKCz in primary rat AM (38) and a rapid membrane localization of PKCz in human myometrial cells (53). A role in regulating vesicle trafficking has been implicated for the atypical PKCs by modulating cytoskeleton reorganization via Rho and Rac small GTPases (56,57) or by direct interaction with Rab2 (81).…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…After the cells were exposed to the experimental conditions, nuclear extracts were prepared and analyzed as described previously (50). The activity of NF-B in the nuclear extracts was determined by EMSA.…”
Section: Methodsmentioning
confidence: 99%
“…SP-A-enhanced aPKC kinase activity in AM has been shown previously to be critically involved in SP-A-mediated IB-␣ stabilization (50). We next investigated SP-A-induced aPKC kinase activity in the presence of Aman, PAO, CPZ, and CytoD in an in vitro immunocomplex kinase assay as described in MATERIALS AND METHODS (Fig.…”
Section: Sp-a-induced Apkc Kinase Activity Requires CCV Formationmentioning
confidence: 99%